Analysis of the Implementation of the "Gass Track Chemotherapy Program" As an Alternative Solution to Improve Oncology Services - Ekowati, Sri Indah; Purnaningsih, Enggar (Journal of Biomedical Sciences and Health, 2026)
Background: Timeliness in chemotherapy scheduling is essential in oncology practice. In Dr. Kariadi Hospital, increasing patient volume led to long waiting lists and treatment delays averaging 7 days. To address this issue, an innovation called "Gass Track," adapted from the fast-track system, was developed to accelerate chemotherapy services. Objective: This study aimed to analyze the implementation of the Gass Track chemotherapy program as an alternative solution to improve service efficiency and timeliness in oncology care at Dr. Kariadi Hospital, Semarang, Indonesia. Methods: This pre-post observational study used retrospective secondary data from January 2023 to June 2024, conducted at the Oncology Installation of Dr. Kariadi Hospital, Semarang. Individual patient-level chemotherapy delay data were extracted from medical records. Data were analyzed to compare chemotherapy delay distributions, patient flow, and service throughput between the pre-implementation (January May 2023) and post-implementation (June 2023 June 2024) periods. Results: A total of 8,479 programmed chemotherapy patients were recorded. Of 6,273 post-implementation patients, 509 (8.1%) received care via Gass Track. The median chemotherapy delay decreased from 7 days (IQR: 6 8) pre-implementation to 4 days (IQR: 3 5) post-implementation. A Mann-Whitney U test on individual patient-level data confirmed the reduction was statistically significant (U = 12,988,890; p < 0.001; rank-biserial r = 0.877, indicating a large effect). Monthly chemotherapy throughput increased by approximately 9.4% (from 441.2 to 482.5 patients/month). Conclusion: Gass Track improved patient flow, reduced delays, and supported timeliness in oncology chemotherapy services without requiring additional resources.